2017
DOI: 10.1144/sp454.12
|View full text |Cite
|
Sign up to set email alerts
|

Integrating induced seismicity with rock mechanics: a conceptual model for the 2011 Preese Hall fracture development and induced seismicity

Abstract: By integrating multiple datasets with relevant theory, covering fluid injection and fracturing, a conceptual model has been developed for the fracture development and induced seismicity associated with the fracking in 2011 of the Carboniferous Bowland Shale in the Preese Hall-1 well in Lancashire, NW England. Key features of this model include the steep fault that has been recognized adjoining this well, which slipped in the largest induced earthquakes, and the presence of a weak subhorizontal 'flat' within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…Production will reduce the fluid pressure in the reservoir being pumped. Fluid pressure changes within faults are well known as a cause of anthropogenic seismicity (e.g., [9,10]); however, rather than a decrease, the causative change is usually an increase in fluid pressure as, for example, for the Preese Hall earthquake sequence in 2011, caused by injection of water under pressure during 'fracking' for shale gas (e.g., [11]).…”
Section: Figurementioning
confidence: 99%
“…Production will reduce the fluid pressure in the reservoir being pumped. Fluid pressure changes within faults are well known as a cause of anthropogenic seismicity (e.g., [9,10]); however, rather than a decrease, the causative change is usually an increase in fluid pressure as, for example, for the Preese Hall earthquake sequence in 2011, caused by injection of water under pressure during 'fracking' for shale gas (e.g., [11]).…”
Section: Figurementioning
confidence: 99%
“…This analysis extrapolated in situ stress measurements made in shallower boreholes to greater depths; the data include the σ H azimuth (with the intermediate principal stress vertical) of 135 ± 3°(S45 ± 3°E) at~700 m depth from hydraulic fractures and 136 ± 4°(S44 ± 4°E) at~800 m depth from drilling-induced fractures [58], these measurements being made in Early Miocene tuff (Table 1) in a borehole~4 km SW of the Pohang EGS site. However, other case studies indicate that such extrapolation cannot be done with confidence, as the stress tensor orientation may change significantly with depth (especially between contrasting lithologies) (e.g., [21,59]), a phenomenon recognized in Korea [57]. For example, Chang et al [56] reported a typical WSW-ENE maximum principal stress and a typical vertical minimum principal stress in SE Korea from measurements in shallow (depth <350 m) boreholes.…”
Section: State Of Stress the Maximum Principal Stress Beneathmentioning
confidence: 99%
“…Three dimensional geomechanics case studies such as this can in principle be analyzed trigonometrically (e.g., [61,62]). However, we have instead used a vector geometry approach [21] as this produces equivalent results with simpler calculations. Searching through the combinations of magnitudes and orientations of the principal stresses proposed by Park et al [15], the focal mechanism by Kim et al [7] (Figure 5(b)) is thus consistent with a maximum principal stress oriented at azimuth N64°E (064°) whereas that by Grigoli et al [6] (Figure 5(c)) is consistent with S76°E (114°).…”
Section: State Of Stress the Maximum Principal Stress Beneathmentioning
confidence: 99%
See 2 more Smart Citations